Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2011)
This last 2011 issue of Studies in Second Language Learning and Teaching brings together four papers dealing with the role of affective factors and different aspects of the knowledge of grammar. In the first of these, Adriana Biedroń reports the results of a study which explored the personality predictors of foreign language aptitude, adopting as a point of reference the Big Five model proposed by Costa and McCrae (1992) and using multiple regression to tap the impact of Openness to Experience, Conscientiousness, Extraversion, Agreeableness and Neuroticism. Subsequently, Małgorzata Baran-Łucarz investigates the relationship between perceived and actual levels of secondary school learners’ command of foreign language pronunciation and their level of classroom anxiety, drawing upon a combination of quantitative and qualitative data for this purpose. In the next contribution, Mojgan Rashtchi and Mahnaz Afzali seek to determine whether the use of activities aimed at raising the awareness of advanced learners of English of the features of spoken grammar aids their comprehension of real-life conversation, as well as to examine their attitudes towards such activities. Finally, Marcin Jaroszek describes the findings of a longitudinal study which focused on the use of conjunctions by advanced learners of English over a three-year period, investigated in relation to the reference level (i.e., native-speaker discourse and teacher talk in English as a foreign language classes), the type of exposure and instructional procedures.